Do We Now Know What Inappropriate Laboratory Utilization Is?: An Expanded Systematic Review of Laboratory Clinical Audits. Issue 6 (1st June 2014) - Hauser, Ronald G.; Shirts, Brian H.
Abstract: Objectives: Many nonpathologists and some pathologists consider utilization review essential to laboratory quality improvement, but (1) confusion surrounding the definition of "appropriate" laboratory utilization, (2) the reliance on manual chart review, and (3) a lack of leadership have contributed to its unstandardized implementation. How the solutions to these barriers have evolved since the 1950s is described. Methods: A systematic literature review is used. Results: Current literature largely defines inappropriate laboratory utilization as any test order in violation of a guideline produced by a government or professional society. Audits performed without manual chart review (ie, database query) have dramatically increased since the mid-1990s. Most utilization audits do not involve any author with a pathology or laboratory medicine affiliation. Conclusions: Literature consensus defining "inappropriate" utilization combined with the adoption of database technology has removed key obstacles to utilization reviews. Leadership is needed to unify and benchmark laboratory utilization.